A calorimetric study of egg white proteins - Ferreira, M. (1997)
Egg white is of great interest for many culinary and industrial applications. Egg white is used for coating, gluing, thickening and so on in pasta, desserts, etc. There is thus a great interest from the industrial point of view to better know this raw material, used in very large amounts in the dessert production for example, and to obtain egg white fractions with different functional properties. Various egg white fractions prepared by selected procedures were analyzed by differential scanning calorimetry (DSC). The products resulting from a given fractionation procedure can thus be described by the thermal denaturation parameters (temperatures and enthalpies) of the egg white proteins. This work demonstrates the interest of the DSC technique and proves that the fractionation procedures selected here give the expected protein fractions.